APLIKASI PENGAMAN RUANGAN DENGAN TEKNOLOGI LASER RANGEFINDER MENGGUNAKAN WEBCAM DAN LASER CLASS 2 - Amalia Puspita Sari (Jurusan Ilmu Komputer / Informatika, FMIPA UNDIP, Semarang, 2013)
One of the primary needs of the people is secure. It required every person, family, neighborhood, office, organizations, political parties and the state. so the author of the study final test by making an Security Application of the Room by Using Technology Laser Rangefinder Using Webcam and Laser Class 2 Devices. These applications are built using waterfall process model, which is one of the software process model that has five workflows: requirements definition, system and software design, implementation and unit testing, integration and system testing, operation and maintenance. The system was developed with the framework Visual Studio 2010, C # language and technology laser rangefinder that is implemented with the support of webcam and laser class 2 devices.